Enhancing Global Education Through Insights into Student Responses in Recount Text Writing - Pratama, Muhammad Naufal Yudha; Mandarani, Vidya (Education and Development Research, 2024)
This qualitative study investigates the responses of 8th-grade students in writing recount texts at SMP Muhammadiyah 4 Porong. Through interviews and analysis of students' texts, the research identifies students' chosen topics, feelings during writing, and difficulties faced. Results indicate that while many students struggle with composing recount texts effectively, they generally express positive feelings towards the task. These findings underscore the importance of teachers in supporting students' learning motivation and addressing writing challenges to enhance their writing skills.